2021
DOI: 10.1038/s41598-021-92667-1
|View full text |Cite|
|
Sign up to set email alerts
|

PGE2 displays immunosuppressive effects during human active tuberculosis

Abstract: Prostaglandin E2 (PGE2), an active lipid compound derived from arachidonic acid, regulates different stages of the immune response of the host during several pathologies such as chronic infections or cancer. In fact, manipulation of PGE2 levels was proposed as an approach for countering the Type I IFN signature of tuberculosis (TB). However, very limited information regarding the PGE2 pathway in patients with active TB is currently available. In the present work, we demonstrated that PGE2 exerts a potent immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…This may explain our previous discovery of SASP as beneficial suppressor of M.tb infection in mice ( 17 ) which clearly reduced PGE 2 formation in the present study. These results are in line with reports by others showing increased PGE 2 levels in TB disease ( 38 , 39 ) and indicate that high levels of PGE 2 may reduce the bacterial clearance ability of macrophages related to the severe inflammatory processes in these phagocytes. In this respect, our current results show that M1-MDM exposed to MTB-CM produced high levels of TNF-α, IL-1β and IL-6 which was also suppressed by SASP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may explain our previous discovery of SASP as beneficial suppressor of M.tb infection in mice ( 17 ) which clearly reduced PGE 2 formation in the present study. These results are in line with reports by others showing increased PGE 2 levels in TB disease ( 38 , 39 ) and indicate that high levels of PGE 2 may reduce the bacterial clearance ability of macrophages related to the severe inflammatory processes in these phagocytes. In this respect, our current results show that M1-MDM exposed to MTB-CM produced high levels of TNF-α, IL-1β and IL-6 which was also suppressed by SASP.…”
Section: Discussionsupporting
confidence: 93%
“…All these findings support the notion that excessive PGE 2 is associated with severe inflammation, persisting tissue damage, and poor bacterial clearance ( 42 ). On the other hand, PGE 2 suppressed the excessive inflammatory immune response of the human host against M.tb infection ( 39 ). In fact, PGE 2 has also been suggested to confer protective responses during TB disease.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that PGE2 augmented the percentage of LC3 + neutrophils and monocytes upon Mtb -Ag stimulation. Furthermore, the exogenous addition of this eicosanoid triggered a functional autophagy flux both in monocytes and lymphocytes from TB patients ( Pellegrini et al., 2021 ). Thus, according to our results, PGE2 might be a new target for the development of novel therapeutic tools to fight Mtb .…”
Section: Autophagy In Tb Patientsmentioning
confidence: 99%
“…However, the immune response against Mtb is highly complex. The outcome of TB infection depends, at least in part, on several immune mediators that display critical temporal roles on the host microenvironment ( Sodhi et al., 1997 ; Ottenhoff et al., 1998 ; Chen et al., 2008 ; Pasquinelli et al., 2009 ; Cooper, 2010 ; Jurado et al., 2012 ; Mayer-Barber et al., 2014 ; Pellegrini et al., 2021 ). It has been suggested that host-directed therapies (HDT) could be untapped strategies as complementary therapies against TB, augmenting the host defences and/or limiting tissue damage associated with infection ( Martínez-Colón and Moore, 2018 ; Wan et al., 2018 ; Xiong et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second immunosuppressive mechanism comprises the action of immune checkpoints and inhibitory receptors, extensively investigated in the context of cancer, albeit more recently during viral and bacterial infections [ 162 , 163 , 164 , 165 ]. Their contribution to brucellosis pathogenesis and persistence remains, so far, an open field.…”
Section: Limiting Host Immunity To Establish Chronic Brucel...mentioning
confidence: 99%